Comparison Between 99mTc-Sulesomab and 18F-FDG PET/CT in a Patient With Suspected Prosthetic Joint Infection. (June 2016) - Albano, Domenico; Bosio, Giovanni; Paghera, Barbara; Bertagna, Francesco
Abstract : Abstract: Diagnosing prosthetic joint infection is difficult; clinical signs and symptoms, laboratory tests, radiography, and joint aspiration are less sensitive and specific. We report a patient with fever and painful bilateral hip prosthesis, who underwent 99m Tc-sulesomab scan showing moderate tracer uptake at the lateral surface of the right thigh and no signs of prosthesis infection. The 18 F-FDG-PET/CT showed high uptake at the soft tissue of the right hip prosthesis and detected a fistula. Moreover PET/CT discovered an initial bone marrow involvement at the right femur. The subsequent fistulography confirmed the fistula, and the patient underwent definitive fistulotomy successfully.